Impact of weather conditions on the windows of opportunity for operation of offshore wind farms in portugal - Silva, N. (2014)
The deployment of offshore wind parks face several challenges. Among them are the difficulties introduced by the atmospheric and sea conditions in accessing those wind parks. A window of opportunity is a timeframe when weather and sea conditions are acceptable and enable to perform specific tasks in the installation and operation/maintenance of the offshore wind park. This study identifies typical time periods of windows of opportunity to access three offshore Portuguese maritime regions. The accessibility conditions also take into account the system type transportation method for local access, namely, rubber boat, boat with OAS or helicopter. It was concluded that Portugal has adequate conditions for offshore site maintenance strategies, with a large number of windows of opportunity, but they are relatively short, therefore the installation of offshore wind parks must be carefully planned. This is an important factor in favor of the offshore wind farm deployments on the country.